Protective Effects of Cuscuta australis Against CCl4-Induced Hepatic Injury in Rats: Antioxidant, Anti-Inflammatory, and In Silico Insights - Baccari, Hanen; Bedoui, Arij; Feriani, Anouar; Bouallegue, Amal; Sahri, Nihad; Khatib, Sohaib; Kharrat, Mohamed; Tlili, Nizar; Sobeh, Mansour; Amri, Moez; Abbes, Zouhaier (Pharmaceuticals (Basel, Switzerland), 2025)
Background/Objectives: The search for new bioactive molecules increasingly extends beyond conventional medicinal plants, highlighting the importance of exploring alternative botanical sources. Parasitic plants represent a promising but underexploited reservoir of pharmacologically relevant compounds. Cuscuta australis (CA), a parasitic species with a history of traditional use, remains poorly characterized. This study aimed to investigate its phytochemical composition and evaluate its antioxidant, anti-inflammatory, and hepatoprotective properties. Methods: The phytochemical profile of CA extract was characterized by LC-MS. Antioxidant capacity was assessed using DPPH and ABTS assays. In vivo hepatoprotection was evaluated in male rats subjected to CCl4-induced hepatotoxicity and treated orally with CA (30 or 60 mg/kg body weight). Biochemical, lipid, oxidative stress, and histological parameters were determined. Molecular docking was conducted to predict the binding of major identified compounds against selected protein targets. Results: CA significantly and dose-dependently improved biochemical and histological markers. At 60 mg/kg, ALT, AST, ALP, and bilirubin were reduced by 32%, 33%, 63%, and 51%, respectively. Lipid metabolism was improved by decreased TC, TG, and LDL-C with increased HDL-C. Antioxidant defense was enhanced through elevated CAT, SOD, and GPx activities, accompanied by reduced MDA levels. TNF-α and IL-6 decreased by 48% and 53%, respectively. Histopathology confirmed hepatoprotection and reduced fibrosis. Docking studies revealed strong binding affinities (−7.07 to −19.20 kcal/mol) for several metabolites, notably quercetin glucoside, diosmetin glucoside, caffeic acid glucoside, feruloylquinic acid, and isorhamnetin glucoside, against CYP450, IL-2, TNF-α, and IL-6. Conclusions: These findings demonstrate that C. australis is a promising source of bioactive compounds with hepatoprotective, antioxidant, antihyperlipidemic, and anti-inflammatory effects, supporting its potential as a natural therapeutic agent.